Biological Applications of Macrocyclic Schiff Base Ligands and Their Metal Complexes: A Survey of the Literature (2005–2019). (22nd July 2020) - Golbedaghi, Reza; Tabanez, Andreia M.; Esmaeili, Somayeh; Fausto, Rui
Abstract : This article aims to provide a survey of biological applications of Schiff base macrocycles and their metal complexes, with emphasis given to the synthesis of the compounds and to their uses as antibacterial and antifungal agents. The literature on the subject, published during the 2005–2019 period, is shortly reviewed. This is an informed report collecting information on the addressed topic in a concise systematic way, and can be expected to be useful as a fast literature catalogue for researchers working on this and related domains. Abstract : This article aims to provide a survey of biological applications of Schiff base macrocycles and their metal complexes, with emphasis given to the synthesis of the compounds and to their uses as antibacterial and antifungal agent.